PENGARUH MODEL PROJECT BASED LEARNING TERHADAP HASIL BELAJAR SUBTEMA BENDA DALAM KEGIATAN EKONOMI - Lutfiyana Dwi Aryani; R Teti Rostikawati; Rukmini Handayani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study aims to determine the influence of the Project Based Learning model on learning outcomes for the object sub-theme in economic activities. The sample for this research was 54 class V students at SD Negeri Mekarsari. Data collection techniques in this research used objective tests. Data collection was carried out to obtain learning outcomes or N-Gain obtained by using pretest and posttest. The results showed that there was an effect of applying the Project Based Learning model to the results of learning the sub-theme of objects in economic activities. This is evidenced by the acquisition of the average N-Gain score for the experimental class, namely 83 and the average N-Gain score for the control class, namely 64. Then the results of the hypothesis test using the t test obtained tcount (18,81) > ttable (2,00665) with dk (degrees of freedom) = 52 and a significant level of 0.05 so that H0 is rejected and Ha is accepted. Based on the results of the study, it can be concluded that there is an influence of the Project Based Learning model on the the object sub-theme in economic activities in class V SD Negeri Mekarsari.